Assessment of the management of medical waste during the Coronavirus epidemic was occurring in Al-Diwaniyah Hospital - Razaq Rahi Hamlan; Alaa Kadhim Jasim; Atheer Kadhim Ibadi (University of Thi-Qar Journal of Science, 2023)
Medical waste is a global issue because of its detrimental effects on societal safety and the environment. Due to its contagious and harmful nature, which can have negative consequences on people and the environment, medical waste treatment is crucial. Objective: assessment of the medical waste management during the Coronavirus epidemic was occurring in Al-Diwaniyah Hospitals. Methodology: A cross-sectional survey was used to carry out the investigation. To randomly select cases, a self-administered Arabic language questionnaire was used. The analysis uses SPSS Version 21. Results: General trash has been accounted for the majority of the waste produced in hospitals, with hazardous medical waste accounting for the second-highest percentage (63%) of waste handlers. In Al-Diwaniyah General Hospital, management levels were subpar, and medical waste management (MW) awareness among the entire medical teams was lacking.. the administrative employees, health professionals, and the cleaning staff did not have the necessary level of understanding concerning medical waste. The report suggests that integrated medical waste management should be clarified, suitable roles should be established, regulatory and legislative departments need to be supported, and increasing the training programs in the that medical institusion